High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Correction: Barriers and facilitators for medical oncologists in the further implementation of mainstream genetic testing in breast cancer care in the Netherlands - Chiem L de Jong; Gina Schijven; Ellen G Engelhardt; Agnes Jager; Margreet G. E. M. Ausems (Familial Cancer, 2025)

Barriers and facilitators for medical oncologists in the further implementation of mainstream genetic testing in breast cancer care in the Netherlands - Chiem L de Jong; Gina Schijven; Ellen G Engelhardt; Agnes Jager; Margreet G. E. M. Ausems (Familial Cancer, 2025)
Only 67% of eligible patients with breast cancer currently undergo genetic testing. Mainstream genetic testing (i.e. healthcare professionals (HCPs) from outside the genetics field providing genetic counselling), also referred to asmainstreaming, leads to increased uptake of genetic testing. Unlike surgical oncologists, medical oncologists have not yet widely adopted mainstreaming. This study aims to identify barriers and facilitators for HCPs, in particular medical oncologists, in advancing the implementation of mainstreaming. Structured interviews were conducted with HCPs (predominantly medical oncologists) using the Constructive Technology Assessment (CTA) framework. Participants were recruited from all regions of the Netherlands, ensuring representation from academic medical centres, teaching hospitals and general hospitals. The interview data was analysed using thematic analysis. In this qualitative study, 12 medical oncologists, three nurse practitioners, three clinical geneticists, two clinical laboratory geneticists and one representative of a health insurer were interviewed. Lack of time and limited knowledge were the most commonly mentioned barriers, whilst effective cross-departmental collaboration and education were the most important facilitators. For medical oncologists specifically, financial compensation for the increased workload and the increasing importance of genetic testing for guiding therapy choices were found to be encouraging factors. This study identified several barriers and facilitators to mainstreaming being implemented by medical oncologists. Education to strengthen oncologists’ skills in discussing germline genetic testing may address knowledge gaps and time barriers. Alongside cross-departmental collaboration, these strategies could streamline genetic testing pathways. Further research should evaluate their implementation and effects on patient experience and equitable access.

P19-24 Risk modeling of mixtures of endocrine disrupting chemicals relevant to human exposure, using zebrafish (Danio rerio) embryo as model organism – the RiskMix project - J.M. Weiss; J. Engelhardt; P. Andersson; E. Golosovskaia; P.E. Leonards; L. Zacari Fanali; S. Örn (Toxicology Letters, 2024)

Comparison of methods to calculate groundwater recharge for karst aquifers under a Mediterranean climate - P Hepach; L Bresinsky; M Sauter; Y Livshitz; I Engelhardt (Hydrogeology Journal, 2024)
Karst aquifers can be particularly vulnerable to human activities and climate change due to their relatively high degree of connection with the surface. This study utilized an ensemble of event-based recharge calculation methods to address the problem of structural uncertainty for the example of the Western Mountain Aquifer (WMA), a Mediterranean karst aquifer located in Israel and the West Bank. Spatially distributed recharge estimates derived from the Soil and Water Assessment Tool (SWAT) and the process-based infiltration model (PIM) were compared to site-specific, empirical regression models. The SWAT and PIM mean annual recharge estimates ranged from 32–34.6% of precipitation, almost equating to the results of empirical regression models (32–36%). Future recharge predictions under the influence of climate change were quantified by parameterizing the SWAT and PIM methods with a downscaled regional climate model of Israel. SWAT predicts a 23% decrease in recharge by 2051–2070 relative to 1981–2001. In contrast, PIM shows a 9% decrease, possibly due to the representation of infiltration through preferential flow pathways and exclusion of surface runoff processes. These divergent projections underline key methodological differences in the representation of hydrological processes. Nevertheless, both methods effectively provided good estimates of groundwater recharge. The recharge rates estimated from the various methods were integrated into MODFLOW to assess their relative impacts on groundwater storage dynamics. The ensemble of MODFLOW projected groundwater storage outputs can provide guidance for sustainable groundwater management in the region.

Precipitation patterns and N availability legacy govern microbial response to rewetting in a plant-soil system - Ilonka C. Engelhardt; Pascal A. Niklaus; Florian Bizouard; David Bru; Marie-Christine Breuil; Nadine Rouard; Arnaud Mounier; Laurent Philippot; Romain L. Barnard (Soil Biology and Biochemistry, 2023)

Estrogen immunomodulatory role during transitory post-breeding endometritis in mares - Joana C Engelhardt; Fabrício D Mozzaquatro; Bruno L Anjos; Rogerio F Dias; Gabriela D Pradella; Camila C Vieira; Fernando S Mesquita (Journal of Equine Veterinary Science, 2023)

Precipitation patterns and N availability alter plant-soil microbial C and N dynamics - Ilonka C. Engelhardt; Pascal A. Niklaus; Florian Bizouard; Marie-Christine Breuil; Nadine Rouard; Florence Deau; Laurent Philippot; Romain L. Barnard (Plant and Soil, 2021)

Toxic effects of lead in plants grown in brazilian soils - Geraldo S. Cândido; Gabriel C. Martins; Isabela C. F. Vasques; Francielle R. D. Lima; Polyana Pereira; Mateus M. Engelhardt; Rayner H. C. L. Reis; João José Marques (Ecotoxicology, 2020)

Evaluation of mercury phytoavailability in Oxisols - Francielle R. D. Lima; Mateus M. Engelhardt; Isabela C. F. Vasques; Gabriel C. Martins; Geraldo S. Cândido; Polyana Pereira; Rayner H. C. L. Reis; Aline O. Silva; Luiz Roberto G. Guilherme; João José Marques (Environmental Science and Pollution Research, 2019)

Ecological plant epigenetics: Evidence from model and non‐model species, and the way forward - Christina L. Richards; Conchita Alonso; Claude Becker; Oliver Bossdorf; Etienne Bucher; Maria Colomé‐Tatché; Walter Durka; Jan Engelhardt; Bence Gaspar; Andreas Gogol‐Döring; Ivo Grosse; Thomas P. van Gurp; et al. (Ecology Letters, 2017)
Growing evidence shows that epigenetic mechanisms contribute to complex traits, with implications across many fields of biology. In plant ecology, recent studies have attempted to merge ecological experiments with epigenetic analyses to elucidate the contribution of epigenetics to plant phenotypes, stress responses, adaptation to habitat, and range distributions. While there has been some progress in revealing the role of epigenetics in ecological processes, studies with non‐model species have so far been limited to describing broad patterns based on anonymous markers of DNA methylation. In contrast, studies with model species have benefited from powerful genomic resources , which contribute to a more mechanistic understanding but have limited ecological realism. Understanding the significance of epigenetics for plant ecology requires increased transfer of knowledge and methods from model species research to genomes of evolutionarily divergent species, and examination of responses to complex natural environments at a more mechanistic level. This requires transforming genomics tools specifically for studying non‐model species, which is challenging given the large and often polyploid genomes of plants. Collaboration among molecular geneticists, ecologists and bioinformaticians promises to enhance our understanding of the mutual links between genome function and ecological processes.

Intravascular Inflammation Triggers Intracerebral Activated Microglia and Contributes to Secondary Brain Injury After Experimental Subarachnoid Hemorrhage (eSAH) - Etienne Atangana; Ulf C. Schneider; Kinga Blecharz; Salima Magrini; Josephin Wagner; Melina Nieminen-Kelhä; Irina Kremenetskaia; Frank L. Heppner; Britta Engelhardt; Peter Vajkoczy (Translational Stroke Research, 2017)

Timing of risk reducing mastectomy in breast cancer patients carrying a BRCA1/2 mutation: retrospective data from the Dutch HEBON study - M. R. Wevers; M. K. Schmidt; E. G. Engelhardt; S. Verhoef; M. J. Hooning; M. Kriege; C. Seynaeve; M. Collée; C. J. van Asperen; R. A. E. M. Tollenaar; L. B. Koppert; A. J. Witkamp; et al. (Familial Cancer, 2015)

Impedance Spectroscopy for the Non-Destructive Evaluation of In Vitro Epidermal Models - F. Groeber; L. Engelhardt; S. Egger; H. Werthmann; M. Monaghan; H. Walles; J. Hansmann (Pharmaceutical Research, 2015)

Lychee tree parameters for water balance modeling - K. Spohrer; C. Jantschke; L. Herrmann; M. Engelhardt; S. Pinmanee; K. Stahr (Plant and Soil, 2006)